B-Learning – An Institutional and Operational Development Tool - Silva, Manuel (2021)
e-Learning has been gaining a huge acceptance among educators, specially in Higher Education Institutions (HEI). This happens due to the exponential growth of the use of Internet and educational technologies that allowed deep transformations in the teaching-learning process and paradigm. Nowadays Internet has been reinforcing its role as a mediator-facilitator platform in education, allowing the creation of new contexts where learning opportunities can be expanded and potencially collaborative and where the resources are widely available. In this context, HEI have great responsibility in granting teacher and student access to suitable educational technologies, in providing the adequate means for the adoption of those tools and in the creation of opportunities for the dissemination of technical knowledge and pedagogical expertise amongst all intervenient. In fact, e-learning has become a competitive factor amongst institutions, and schools are confronted with the need to realign their mission, by developing and implementing different initiatives and projects so as to support and motivate teachers and to offer today’s students complementary means for the acquisition of knowledge and skills. In this paper we will analyse the case the Online Support Project (PAOL) and the approach followed by the School of Accounting and Administration of Oporto (ISCAP). The main goals of PAOL are to provide the implementation of computer assisted education at ISCAP in a blended learning model and to assist teachers and students in their adjustment to educational technologies, by developing training opportunities and resources, offering technical facilities and sharing good practice. The project began its activity in 2003 with WebCT, but soon changed its approach with the adoption of the open source platform Moodle and the integration of specialized staff to assist teachers and students on a daily basis. Since then, the b-learning model that PAOL initiated has been maturing the school’s educational culture, according to the teacher’s willingness or availability to integrate technology in the teaching-learning process. The use of Web technologies follows a similar trend to that of Roger’s diffusion of innovation theory, as it developed due to the enthusiasm of some innovators and grew steadily in adepts, having now 162 teachers who use Moodle on a regular basis. Teacher’s role in this process can be classified into different types, having, for instance, teachers that are keener to participate and integrate technology, teachers that only allow themselves to participate if the experience is proven successful by others and teachers that are reluctant to participate in any form. It is important to analyse the impact of these roles in the institutional development of b-learning so that we can develop new solutions and approaches that better meet the expectations of the institution. Thus, this paper will focus on the knowledge acquired throughout the experience in the use of Moodle by PAOL at ISCAP throughout the years (2003-2009), as well as the collaborative and cooperative relationships that have been established between teachers, students and the use of b-learning educational approaches and technology.